Recurrent ovarian hemorrhage in a patient with aplastic anemia: A case report. Issue 27 (July 2018) - Yang, Hua-Di; Xia, Meng-Ting; Shao, Yi-Feng; Ying, Pian
Abstract: Rationale: Recurrent ovarian hemorrhage resulting in ovarian infarction may lead to a life-threatening intraperitoneal hemorrhage in women with bleeding disorders such as aplastic anemia (AA). Moreover, it is seen as ovarian tumors in the diagnosis. The authors report a clinical case with the aim of sharing our experiences and exploring the ways to diagnose, treat, and avoid ovarian hemorrhage. Patients concerns: A 48-year-old woman with AA had suffered from a serious abdominal distension for the past 24 hours, which had occurred intermittently for the past 15 years. Diagnoses: Pelvic ultrasonography had revealed a large anechoic area of fluid in the abdomen without any sign of primary hemorrhage each time she had experienced an episode over the past 15 years. The volume of pelvic fluid had decreased after anti-inflammatory and hemostatic treatment. At presentation, the abdominal computed tomography suggested an ovarian tumor with a massive hemoperitoneum (a right ovarian mass, 5.7 × 5.0 × 5.0 cm 3 in size, with a large amount of abdominal and pelvic fluid). Interventions: Surgery was performed with respect to the bilateral uterine adnexa. On laparotomy, there were blood clots of approximately 6.0 × 6.0 × 5.0 cm 3 surrounding the right ovary and approximately 400 mL bloody fluid in the abdomen. Outcomes: The patient recovered without incident and was transferred to a hematology ward 1 week later. Postoperative pathology confirmed hemorrhagic infarction of the right ovary. Lessons: In conclusion, continuous ovarian bleeding can cause ovarian infarction to women with bleeding disorders and it may be confused with an ovarian tumor. Moreover, an earlier ovariectomy procedure under stable conditions or treatment with gonadotropin-releasing hormone that prevent bleeding via ovulation suppression may be effective for such cases.